Pengaruh Lama Perendaman dengan Sari Labu Siam (Sechium edule) Terhadap Penurunan Kafein Biji Kopi Arabika (Coffea arabica) Kintamani - Dewi, Komang Puspita; Nocianitri, Komang Ayu; Hatiningsih, Sayi (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 12 No 4 (2023): Jurnal ITEPA, 2023)
The process of decaffeination involves reducing the caffeine content in coffee and other substances containing caffeine using various methods, such as immersing them in siamese pumpkin extract. Siamese pumpkin extract contains protease enzymes that aid in the decaffeination process. This research aims to investigate the impact of soaking time with siamese pumpkin extract on decreasing the caffeine content of Kintamani arabica coffee beans and to determine the appropriate soaking duration for reducing the caffeine content of Kintamani arabica coffee. In this study, a Completely Randomized Design was employed with five levels of soaking time treatments, namely 0 hours, 12 hours, 24 hours, 36 hours, and 48 hours, which were repeated three times, resulting in 15 experimental units. The parameters observed included water content, protein content, caffeine content, and sensory evaluation, including aroma, taste, and overall acceptance. The data were analyzed using analysis of variance (ANOVA), and if there was a significant effect of the treatment, Duncan's multiple range test was applied. The duration of soaking Arabica Kintamani coffee beans with siamese pumpkin extract had a significant influence on the water content, protein content, caffeine content, and sensory attributes of the coffee. The optimal soaking time for producing decaffeinated coffee was found to be 24 hours, resulting in a caffeine content of 0.3% and a water content of 2.72%, with a protein content of 22.14%. The sensory evaluation revealed that the coffee had a light coffee aroma and a light bitter taste, which was preferred overall.